Pyrethrum extract encapsulated in nanoparticles: toxicity studies based on genotoxicity and hematological effects in bullfrog tadpoles - Oliveira, C. R.; Garcia, T. D.; Franco-Belussi, L. [UNESP]; Salla, R. F.; Souza, B. F. S.; Melo, N. F. S. de; Irazusta, S. P.; Jones-Costa, M.; Silva-Zacarin, E. C.M.; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2019)
The environment receives a large amount of pesticides annually, about 2.7 kg/ha per year are used in crop production, having a negative impact on the environment and biodiversity, for example, physiological effects on non-target species. Advances in technology and nanocarrier systems for agrochemicals have led to new alternatives to minimize these impacts, such as nanopesticides, which are considered more efficient, safe and sustainable. However, it is important to evaluate the risk potential, action and toxicity of nanopesticides in aquatic and terrestrial organisms. This study aims to evaluate genotoxic and hematological biomarkers in bullfrog tadpoles (Lithobates catesbeianus) submitted to acute exposure (48h) to pyrethrum extract (PYR) and solid lipid nanoparticles loaded with PYR. Results showed increased number of leukocytes changed significantly during short-time exposure, specifically eosinophils in nanoparticle-exposed groups and basophil in PYR-exposed group. Hematological analysis showed that PYR encapsulated in nanoparticles significantly increased the erythrocyte number compared to the other exposed groups. Data from the comet assay indicated an increase in frequency of the classes that correspond to more severe DNA damage in exposed groups, being that the PYR-exposed group showed a high frequency of class 4 DNA damage. Moreover, erythrocyte nuclear abnormalities were triggered by short-time exposure in all treatments, which showed effects significantly higher than the control group. These results showed genotoxic responses in tadpoles, which could trigger cell death pathways. These analyses were interesting for applications in contamination in aquatic environments and biomonitoring, because will evaluate the toxicity in species and environmental contamination. However, to better understand the effects of nanopesticides and botanical insecticides on non-target organisms’ further studies are needed in order to contribute to regulatory aspects of future uses for these systems
Keywords: Nanotoxicology; Solid lipid nanoparticles; Botanical insecticides; Pyrethrum; Amphibian; Genotoxicity